PENGEMBANGAN MODUL IPA TERPADU BERBASIS LITERASI SAINS PADA MATERI TEKANAN ZAT - MAYA PUJOWATI; YUSUF BUNGKANG; ALBERT LUMBU (Jurnal Ilmu Pendidikan Indonesia, 2020)
This research is research and development with the aim to find out how to develop integrated science learning modules based on scientific literacy in the material pressure of eighth grade Madrasah Tsanawiyah Darul Dakwah Wa'Irsyad (DDI) students in Jayapura. The number of samples in this study 25 with descriptive descriptive data analysis techniques to determine the feasibility of the module. The results showed that: (1) Module development with the stages of information gathering, planning, development, validation and testing; (2) The feasibility of the prepared learning module, based on the validator of the material obtained an average of 90% with a feasible category, the validator of the media obtained an average of 91% with a feasible category, while the results of the responses of students with an average of 77.76% with quite interesting categories, (3) There is an increase in the learning outcomes of students in class VIII by learning to use an integrated science module material pressure based on scientific literacy with n-Gain RPP-1 values of 0.61, RPP-2 of 0.71, RPP-3 of 0.91, RPP-4 of 0.71, RPP-5 is 0.80, and n-gain is on average 0.80 with high category